The Key Role of the Drug Self-Aggregation Ability to Obtain Optimal Nanocarriers Based on Aromatic-Aromatic Drug-Polymer Interactions - Guerrero-Nunez, J; Guerrero-Nunez, J (Elsevier B.V., 2021)
The efficient association and controlled release of hydrophilic and aromatic low molecular-weight drugs (HALMD) still remains a challenge due to their relatively weak interactions with excipients and strong affinity to water. Considering that a wide variety of drugs to treat chronic diseases are HALMD, their inclusion in polymeric nanoparticles (NPs) constitutes an attractive possibility by providing to these drugs with controllable physiochemical properties, preventing crisis episodes, decreasing dose-dependent side effects and promoting therapeutic adhesiveness. However, the strong interaction of HALMD with the aqueous medium jeopardizes their encapsulation and controlled release. In this work, the role of the self-assembly tendency of HALMD on their association with the aromatic excipient poly(sodium 4-styrensulfonate) (PSS) to form NPs is studied. For this aim, the widely used drugs amitriptyline (AMT), promethazine (PMZ), and chlorpheniramine (CPM) are selected due to their well described critical aggregation concentration (cac) (36 mM for AMT, 36 mM for PMZ, and 69.5 mM for CPM). These drugs undergo aromatic-aromatic interactions with the polymer, which stabilize their mutual binding, as seen by NMR. The simple mixing of solutions of opposite charged molecules (drug + PSS) allowed obtaining NPs. Importantly, comparing the three drugs, the formation of NPs occurred at significantly lower absolute concentration and significantly lower drug/polymer ratio as the cac takes lower values, indicating a stronger binding to the polymer, as also deduced from the respective drug/polymer dissociation constant values. In addition, the number of formed NPs is similar for all formulations, even though a much lower concentration of the drug and polymer is present in systems comprising lower cac. The obtained NPs are spheroidal and present size between 100 and 160 nm, low polydispersity (≤0.3) and negative zeta potential (from −30 to −60 mV). The association efficiency reaches values ≥ 83% and drug loading could achieve values up to 68% (never evidenced before for systems comprising HALMD). In addition, drug release studies are also significantly influenced by cac, providing more prolonged release for AMT and PMZ (lower cac), whose delivery profiles adjust to the Korsmeyer-Peppas equation. As a novelty of this work, a synergic contribution of drug self-association tendency and aromatic-aromatic interaction between the drug and polymers is highlighted, a fact that could be crucial for the rational design and development of efficient drug delivery systems. © 2021 Elsevier B.V.